Rate of remission after radio-ablative iodine therapy for thyrotoxicosis: The University Kebangsaan Malaysia Medical Centre (UKMMC) experience - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; AbAziz, Aini; Rajoo, Subashini; Loh, Huai Heng; Ooi, Chew Peng; Wan Seman, Wan Juani; Omar, Mohd Rahman; A Wahab, Norasyikin; Zainuddin, Suehazlyn; Mustafa, Norlaila; Sukor, Norlela; et al. (Malaysian Endocrine and Metabolic Society, 2014)
Objectives: To describe the rate of remission of thyrotoxicosis after radioablative iodine-131 (RAI) therapy. Methods: This was a retrospective review of 84 thyrotoxic patients who received RAI in the year 2011/2012. Their blood investigations prior and post-RAI therapy were reviewed. Data were analyzed using SPSS 19. Results: Eighty-four patient received RAI therapy in 2011/2012 and was followed-up till March 2014. The mean age of the patients was 45.8 ± 12.8 years. Majority (57.1%) received 12 mCi, 19% received 15 mCi and 23.8% received lower dose (10 mCi) of RAI. Mean thyroxine level prior to RAI was 28.3 ± 12.0 pmol/L, and majority (77.8%) had suppressed TSH (<0.01 mIU/L) and 22.2% had low but detectable TSH (0.01-0.3 mIU/L). Fourtyfive percent (44.9%) remained hyperthyroid at 6 months post RAI (44.2% have suppressed TSH, 55.8% have detectable low TSH). Among those who went into remission at 6 months, 31.6% were euthyroid and 68.4% were hypothyroid. At 12 months 51.2% of patient goes into remission where 39.5% of them were euthyroid and 60.5% were hypothyroid. Half of the patient went into remission by 5 months post RAI therapy. By 24 months, 81.9% had gone into remission. Conclusions: The percentage of remission after RAI therapy at our centre increases with duration. By 24 months RAI induces remission in about 82% of patients